Quantitative assessment of synergistic effects in push-pull tactical ventilation during nonlinear space fires - Pei Wang; Yanbo Yin; Wenju Liu; Gang Wang; Yunchao Bai; Changyuan He (PLoS ONE, 2026)
Smoke generated in compartment fires rapidly degrades visibility and tenability, making mechanical tactical ventilation a critical measure for restoring operable conditions. This study provides a full-scale experimental assessment of the mechanical (fan-driven) component of tactical ventilation in a two-story, non-linear layout with stairwell connectivity. Following the cold-flow experimental methodology established in prior PPV studies, smoke was produced using commercially available simulated smoke cakes to generate cold, thereby isolating the aerodynamic ventilation performance from buoyancy-driven fire dynamics. The performance of positive pressure ventilation (PPV), negative pressure ventilation (NPV), and their coordinated push-pull operation was quantified using illuminance recovery, local airspeed measurements at openings, and clearance time to 90% illuminance recovery. Each condition was repeated three times. Results show that the push-pull mode achieved the shortest mean clearance time (101.4 ± 16.9 s, mean ± SD, n = 6), reducing clearance time by approximately 25.0% compared with PPV (135.1 ± 15.9 s) and 31.9% compared with NPV (149.0 ± 15.9 s). One-way ANOVA on the overall clearance time confirmed statistically significant differences among the three conditions (F(2,15) = 13.67, p < 0.001). However, the synergy gain factor (SGF = 0.666) indicates sub-linear gains relative to ideal linear superposition. Importantly, the findings are intended as a ventilation-driven baseline relevant to training scenarios and post-knockdown smoke management where thermal driving is reduced; extrapolation to fully developed fires requires coupled thermal-fluid validation.